PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTUAN MEDIA CANVA TERHADAP KETERAMPILAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMK NEGERI 8 PADANG - Oktavia, Aisyah; Domi Fella Henanggil , Mita; R, Syarul; Arma Putri, Delsy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to describe the following three things. First, to describe the level of biographical text writing skills of class X students of SMK Negeri 8 Padang before using the project based learning model assisted by Canva media. Second, to describe the level of biographical text writing skills of class X students of SMK Negeri 8 Padang after using the project based learning model assisted by Canva media. Third, to analyze and explain theoretically and practically the effect of the project based learning model assisted by Canva media on the biographical text writing skills of class X students of SMK Negeri 8 Padang. This type of research is quantitative with an experimental research method. The design of this study is one group pretest and posttest design. The research sample was taken using a purposive sampling technique, namely class X Kriya 1 students as a sample totaling 36 people. Based on the research conducted, the use of the project based learning model assisted by Canva media in learning to write biographical texts shows a significant difference in improving students' biographical text writing skills. Before using the project based learning model assisted by Canva media, the value of students' biographical text writing skills was 77.66, which is in the Good (B) qualification. This indicates that students are not yet skilled at writing biographical texts. However, after using the project-based learning model with the aid of Canva, students' biographical writing skills scored 83.68, ranking them as Good (B). Therefore, it can be concluded that the project-based learning model with the aid of Canva is suitable as an effective learning model for improving biographical writing skills.